Adsorption and Decomposition of Lignin Model Molecules: the Veratrol Family. A Surface Science Approach. - Asiri, Mohammed (Université d'Ottawa / University of Ottawa, 2019)
The growth of the World’s population always comes with a higher demand of energy. Covering this demand requires finding new energy sources and especially ones that manage the risks of further global warming. Biomass energy is considered as one of the clean energy resources, and widely available. Lignin is a lignocellulosic biomass polymer that constitutes the second most abundant polymer in biomass. The interest of lignin in science laboratories is due to its availability and sustainability that could produce a new supply of fuels and valuable chemicals. Among the different methods of lignin conversion into fine chemicals, heterogeneous catalysis seems to be a perfect method because it reduces the activation energies for reaction and it separates the product from the catalyst. In this work, the conversion of lignin by a heterogeneous catalyst was explored under ultrahigh vacuum conditions using three surface science techniques: Infrared Reflection Absorption Spectroscopy, X-ray Photoelectron Spectroscopy, and Temperature Programmed Desorption. Because of the difficulties of using lignin under UHV conditions due to its physical properties, lignin model molecules with the same chemical structure are the only way to gain better understanding of lignin reactivity. In the present work, Veratrol, 1,3-dimethoxybenzene, and 1,4-dimethoxybenzene were used on Pt(111) surface as lignin models. The reactivity of veratrol on Pt(111) showed the formation of 1,2-benzoquinone by the dehydrogenation of the two methyl groups, which gave three desorption products: catechol (observed here for the first time), hydrogen, and carbon monoxide. The isomers 1,3 and 1,4 desorbed hydrogen and carbon monoxide of their monolayer desorption predictably. 1,3-dimethoxybenzene showed the formation of benzene at certain temperatures. 1,4-dimethoxybenzene adsorbed on Pt(111) via the carbon species of its aromatic ring. The three isomers show slightly different adsorption geometries which lead to rather different decomposition pathways. This study of such complex behavior is a great example of the sensitivity of selectivity in heterogeneous catalysis, even for very similar isomers. The detailed thesis is a continuous work of the route forwarding lignin valorization by increasing the complexity of the models of lignin.
Keywords: IRAS; Veratrol